2012
DOI: 10.1530/eje-11-1095
|View full text |Cite
|
Sign up to set email alerts
|

MANAGEMENT OF ENDOCRINE DISEASE: The burden of Cushing's disease: clinical and health-related quality of life aspects

Abstract: Objective: Cushing's disease (CD) is a rare endocrine disorder characterized by excess secretion of ACTH due to a pituitary adenoma. Current treatment options are limited and may pose additional risks. A literature review was conducted to assess the holistic burden of CD. Design: Studies published in English were evaluated to address questions regarding the epidemiology of CD, time to diagnosis, health-related quality of life (HRQoL), treatment outcomes, mortality, prevalence of comorbidities at diagnosis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
202
1
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(220 citation statements)
references
References 125 publications
(187 reference statements)
5
202
1
12
Order By: Relevance
“…However, these maximum rates of remission can be considered to be overestimations of the true outcomes of Cushing's disease after initial microscopic TSS, because the potential for relapse remains high. In this review, the reported rates of recurrence ranged from 5.0 to 47.4%; similarly, rates of 5-36% were also reported in a recent publication (61). The wide range of rates of remission and recurrence observed highlight the fact that statistics for treatment outcomes are dependent on the criteria used to define those outcomes.…”
Section: Discussionsupporting
confidence: 69%
“…However, these maximum rates of remission can be considered to be overestimations of the true outcomes of Cushing's disease after initial microscopic TSS, because the potential for relapse remains high. In this review, the reported rates of recurrence ranged from 5.0 to 47.4%; similarly, rates of 5-36% were also reported in a recent publication (61). The wide range of rates of remission and recurrence observed highlight the fact that statistics for treatment outcomes are dependent on the criteria used to define those outcomes.…”
Section: Discussionsupporting
confidence: 69%
“…Hypercortisolemia-associated morbidities, particularly increased cardiovascular risk, may persist in a substantial number of CS patients despite normalization of hypercortisolemia (3,4). Increased mortality and morbidities like hypertension, hyperglycemia, increased fat mass, hypercoagulability, decreased bone mineral density and quality, psychopathologies, and cognitive impairment significantly improve after successful treatment of CS, but even after long-term remission, these morbidities and mortality may not be completely reversible (5). Therefore, early diagnosis and treatment is important before the presentation of overt cardiovascular, metabolic, and psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…(pituitary adenoma) [1][2][3][4][5] . Patients with CD experience a remarkably broad spectrum and high prevalence of comorbidities associated with chronic hypercortisolism, and diagnosis of CD is challenging in part because of the many disparate manifestations of the disease 2 .…”
mentioning
confidence: 99%
“…The many comorbidities associated with CD include ischemic heart disease, obesity, hypertension, impairment of glucose tolerance, dyslipidemia, and thrombotic diathesis 3,[12][13][14] , which together increase cardiovascular risk. Other comorbidities found among CD patients include infections (urinary tract infections and pneumonia), psychopathologies (anxiety, depression, and cognitive deficit), as well as skeletal problems (fractures and osteoporosis) 3,[12][13][14] .…”
mentioning
confidence: 99%
See 1 more Smart Citation